KEBERAGAMAN SERANGGA PADA TANAMAN BUAH NAGA (Hylocereus polyrhizus) (STUDI KASUS DI SAREE, ACEH BESAR) - fridayati, diah (Pro-STek, 2025)
The diversity of insects is crucial in an agricultural ecosystem. In dragon fruit-based agriculture (Hylocereus spp.), the presence of insects has both positive and negative impacts on crop productivity. Dragon fruit, a type of cactus originating from Mexico, is now widely cultivated in many regions worldwide, including Indonesia. With rapid growth in Saree, Aceh Besar, one of the main challenges in dragon fruit farming is plant pests (OPT), which cause yield reduction and increased production costs. The purpose of the research is to describe the diversity of insects on dragon fruit (Hylocereus Polyrhizus) plants. The survey method used is purposive sampling, conducted on a dragon fruit plantation. The study results showed that the insects found in the dragon fruit plantation consisted of 9 insect orders and 48 insect families: Order Araneae, Order Blatodea, Order Coleoptera, Order Dermaptera, Order Diptera, Order Hemiptera, Order Hymenoptera, Order Isoptera, and Order Lepidoptera. Order Diptera had the largest representation, followed by Order Hymenoptera. The most abundant insect individuals were Ichneumonidae and Braconidae insects. Keywords: Insect Population, Ichneumonidae, Braconidae, Dragon Fruit Plants